Peculiar electric properties of polarized layer in alkaline silicate glasses. Issue 5 (19th January 2022) - Koroleva, Ekaterina; Reshetov, Ilya; Babich, Ekaterina; Vakhrushev, Sergey; Tagantsev, Dmitry; Lipovskii, Andrey
Abstract: Broadband dielectric spectroscopy (BDS) was applied to study polarization phenomena in alkaline silicate glasses, in particular, properties and structure of subsurface (anodic) polarized layers forming in poling with deposited film electrodes of different structures. A model of poled glasses which does not contradict experimental data is proposed. In accordance with the model, a poled glass is presented as two resistor‐capacitor circuits in a series connection, one of which is the polarized layer and another is the rest of the sample. It is found that the electric properties of the layers essentially depend on the structure of the anodic electrode used in glass poling. It is also shown that the dielectric response of poled glass samples is mainly determined by the electric properties of the submicron polarized layers and this gives an opportunity to reveal specific properties of the layers rather than ones of the glass sample bulk. Revealed temperature dependence of DC conductivity of the polarized layers obeys Arrhenius's law, and determining activation energy does not depend on the electrode. Finally, it is noted that today above‐mentioned information about polarized layers can be obtained only by BDS.